Addition of V-Stage to Conventional TNM Staging to Create the TNVM Staging System for Accurate Prediction of Prognosis in Colon Cancer: A Multi-Institutional Retrospective Cohort Study - Jung Hoon Bae; Ji Hoon Kim; Jaeim Lee; Bong-Hyeon Kye; Sang Chul Lee; In Kyu Lee; Won Kyung Kang; Hyeon-Min Cho; Yoon Suk Lee (Biomedicines, 2021)
We evaluated the prognostic impact of vascular invasion (VI) compared with nodal (N) stage and developed a new staging system including VI in colon cancer. Patients who underwent curative resection with stage II-III colon cancer were assigned to VI and non-VI groups; the latter was subclassified as N0, N1, and N2; a new TNVM staging was devised by adding the V-stage. Among the 2243 study participants, the VI group independently showed worse oncological outcomes than the N1 group (disease-free survival (DFS), hazard-ratio (HR) 1.704, 1.267–2.291; overall survival (OS), HR 2.301, 1.582–3.348). The 5-year DFS in the VI group was 63.4% [N1b (74.6%), p = 0.003; N2a (69.7%), p = 0.126; and N2b (56.8%), p = 0.276], and the 5-year OS was 76.6% [N1b (84.9%), p = 0.004; N2a (83.0%), p = 0.047; and N2b (76.1%), p = 0.906]. Thus, we considered VI as N2a in TNVM staging; 78 patients (3.5%) underwent upstaging. The 5-year OS rates of stage IIB and IIC increased from 88.6% and 65.9% in TNM staging to 90.5% and 85.7% in TNVM staging, respectively. In stage II–III colon cancer, VI had a similar prognostic impact as the N2 stage without VI. The incorporation of the V-stage into the conventional TNM staging facilitates better prediction of prognosis.